CIAT- ACIAR gender workshop: Strengthening the gender lens in agricultural production and value-chain research in Vietnam - International Center for Tropical Agriculture; Australian Centre for International Agricultural Research (2016)
Farming systems in Vietnam are undergoing rapid change, including increased levels of commercialisation and market integration, adoption of (or desire for) labour efficient technologies, and migration of youth in response to non-farm work opportunities. These processes are not only shaping rural landscapes and communities, but challenging traditional gender roles.